Nghiên cứu đặc điểm phản ứng phân hủy 2,4-dinitrotoluen, nitro glycerin trong môi trường nước bằng tác nhân fenton - Quảng, Đoàn Song; Khuê, Đỗ Ngọc; Hưng, Đào Duy; Tấn, Đinh Ngọc (Vietnam Journal of Chemistry, 2015)
This paper introduces the research results on the oxidative decomposition reaction characteristics of 2,4-dinitrotoluen (DNT), nitroglycerin (NG) pollution in water by the Fenton agent. The obtained results showed that Fenton process could decompose DNT and NG. Test results also showed that the decomposition reaction DNT and NG by Fenton agents follow the rules of pseudo first-order reaction and the rate of decomposition of DNT larger decay rate NG.